Correlation between PLR and NLR with Tumor Size in Breast Cancer Patients - Sri Widyaningsih; Zelly Dia Rofinda (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Breast cancer is the most common malignancy in females globally and one of the main causes of cancer death. There are several markers of cancer-related inflammation to help predict the relationship between pathologic characteristics of breast cancer. The research objective was to analyze the correlation between PLR and NLR with associated tumor size in breast cancer. This was a retrospective study with a cross-sectional design. This study used secondary data from the medical records of breast cancer patients who met the inclusion criteria at Siti Khodijah Hospital, Sidoarjo from January 2021 to March 2023. The sample size was 54 subjects, patients with breast cancer confirmed by pathology anatomy. The exclusion criteria were patients with infection, autoimmune disease, and hematology disorder. All the subjects were female. The mean age at the time of breast cancer diagnosis was 50.18±10.23 years, range of 27-80 years old. Most of the patients were over 50 years as much as 28 (51.85 %), while there were 26 (48.14%) > 50 years. The PLR range was 15.45-600.0, the NLR range was 0.58-9.98, tumor size range was 0.5-10.0 cm. Correlation between PLR and NLR with tumor size in breast cancer (p=0.351 and p=0.339). Correlation analysis showed that PLR and NLR had no significant correlation with tumor size ( r= -0.129, p=0.351 and r= -0.133, p=0.339). In conclusion, there is no significant correlation between PLR and NLR with histopathology of tumor size in patients with breast cancer.